Variation in the quality of forage grazed by pregnant/lactating beef cows at key periods in the year - E.S. Vanzant; R.C. Cochran; T.A. Stanley (Kansas Agricultural Experiment Station Research Reports, 1992)
Seven ruminal and esophageally fistulated crossbred beef cows were used to monitor changes in chemical composition of tallgrass-prairie forage selected during November of 1989 and January, March, June, and August of 1990. Quality of forage selected by beef cows was lowest during the period just before calving (cows calved in early February) but had begun to improve by the March sampling (postpartum period) and reached its peak during June sampling period (breeding season). Observed variability in the fiber and protein components of grazed forage highlights the dynamic nature of forage quality and emphasizes the importance of using such information when assessing the nutritional adequacy of range diets.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Beef cows; Range; Forage; Protein; Fiber; Selection